2011
DOI: 10.2528/pier11042703
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Broadband Directional Couplers Using Microstrip With Dielectric Overlay in Millimeter-Wave Band

Abstract: Abstract-Nowadays, millimeter-wave systems are being a key factor to develop wide band applications. In this paper, a directional coupler in millimeter-wave band using dielectric overlay is presented. This leads us to technology aspects, in directional coupler design, are key points to achieve the proper response of the circuit. The coupler proposed in this paper covers the 15-45 GHz band and its response has 15-dB coupling-level, 1-dB coupling-ripple and a reflection coefficient better than 10 dB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…The first one is a 10 dB asymmetric five-section slot-coupled directional coupler, that operates from 1.2 to 12 GHz. It offers a high coupling accuracy of 10 ± 0.6 dB and return loss and isolation better than 23 dB and 28 dB respectively, improving previously reported results in terms of fractional bandwidth and performance [2,[4][5][6]. The second one is a three-section symmetric quadrature hybrid similar to the coupler recently used to realize a high performance six-port IQ demodulator with full UWB coverage [19].…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…The first one is a 10 dB asymmetric five-section slot-coupled directional coupler, that operates from 1.2 to 12 GHz. It offers a high coupling accuracy of 10 ± 0.6 dB and return loss and isolation better than 23 dB and 28 dB respectively, improving previously reported results in terms of fractional bandwidth and performance [2,[4][5][6]. The second one is a three-section symmetric quadrature hybrid similar to the coupler recently used to realize a high performance six-port IQ demodulator with full UWB coverage [19].…”
Section: Introductionmentioning
confidence: 54%
“…Besides, as it will be shown in Section 3, the introduction of corrugations in the slot does not significantly affect the modal impedances. Therefore, this technique makes it possible to develop a more robust design strategy than previously reported methods [2,3,5,6,11], since it allows the phase velocity equalization problem to be decoupled from the classical TEM coupler design based on the selection of adequate impedance values for the sections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of many advantages, these antennas suffer from some disadvantages which include their low efficiency, low power, high Q, poor polarization purity, spurious feed radiation and very narrow bandwidth [11][12][13][14][15][16][17]. There have been some efforts spent using various techniques to improve the performance of such antennas for their widespread applications.…”
Section: Introductionmentioning
confidence: 99%
“…Directional coupler is a fundamental component especially in microwave measurement system [1,2]. References [3][4][5] reported that because of the relative stable structure and properties of rectangular waveguide directional coupler, it was extensively used in microwave engineering to monitor, measure and separate incident power, etc.…”
Section: Introductionmentioning
confidence: 99%